Radiograph’s reject rate among Universiti Kebangsaan Malaysia dental undergraduates and its implications - Azizah Ahmad Fauzi; Ng, Charisza Tze Xin; Wong, Li Li; Ho, Sin Yin; Atika Ashar (Penerbit Universiti Kebangsaan Malaysia, 2021)
The aim of this study was to evaluate the reject rate of periapical and bitewing radiographs among dental undergraduate students of Universiti Kebangsaan Malaysia (UKM), identify the type of radiographic errors which are frequently encountered and compare reject rates between Year 3, Year 4 and Year 5 dental undergraduates. 118 rejected periapical radiographs and 27 rejected bitewing radiographs were collected from the UKM dental undergraduates’ polyclinics for a duration of 10 months. These rejected radiographs were further evaluated to determine the type of radiographic error. A spiking increase in periapical radiographs reject rate from Year 3 (4%) to Year 4 (11%) was observed. This finding was consistent with the statistically significant difference in the periapical radiographs reject rates for Year 3 and Year 4 (p = 0.0475). In periapical radiographs, the most frequently committed radiographic error was apical cut, followed by high density film. Vice versa, high density film was accounted as the most common radiographic error in bitewing radiography. Analysis of periapical and bitewing radiographs’ reject rates among UKM dental undergraduate entails the necessity to supervise undergraduate students regardless of the year of their undergraduate training in all aspects of the radiographic procedures which include positioning radiographic armamentarium, the setting of radiographic exposure time and the film processing procedure.